Crack growth in masonry: Numerical analysis and sensitivity study for discrete and smeared crack modelling. (15th June 2018) - Bejarano-Urrego, Leidy; Verstrynge, Els; Giardina, Giorgia; Van Balen, Koen
Highlights: Modelling of cracking of a full scale masonry wall subjected to three-point bending. Calibration and numerical analysis for discrete and smeared crack modelling. Sensitivity study of a discrete meso-model and continuum smeared macro-model. Identification of critical material parameters affecting non-linear numerical models. Abstract: One of the most common obstacles faced by engineers when making numerical models to assess damage in historical masonry lies in defining the most suitable constitutive models when there is shortage of either material characterization or experimental data. This paper presents the implementation of a 2D finite element model (FEM) of a masonry wall by means of two strategies: a discrete cracking meso-model and a continuum smeared cracking macro-model. A sensitivity study is performed to investigate the effect of material properties variation on both modelling strategies, each of which considers the highly non-linear behaviour as well as the brittle cracking of the masonry. The numerical models are validated through the results obtained from an experimental testing campaign which considered a brick masonry wall subjected to cyclic three-point bending. The results of both modelling strategies compared with experimental results are presented, as well as the criteria considered for material characterization and the sensitivity analysis. Results indicate the suitability of both models to reproduce experimentally observed load capacity, failure mechanism and horizontal deformations. However, the meso-model showed higher accuracy in terms of failure mechanism and plastic deformations. The sensitivity analysis indicated that some material parameters, such as fracture energy, cohesion and tensile strength, significantly govern the final cracking. This is an important criterion for adequately choosing the parameters for further models in which crack width is considered, e.g. for settlement-induced cracking analysis.